2020
DOI: 10.1016/j.ajoc.2020.100871
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive imaging of a choroidal macrovessel

Abstract: Purpose To describe novel anatomic findings of an apparent choroidal macrovessel, originally misdiagnosed as a choroidal tumor, using non-invasive imaging tools. Observations Initial ophthalmic examination revealed an elevated hypopigmented choroidal mass in the macular area, with a serpentine track extending temporally to the equator. Enhanced depth imaging optical coherence tomography (EDI-OCT) revealed an optically hollow lesion just outside the choroid-scleral junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…CM is predominantly observed in the middle age to older Caucasian women [ 4 ]. However, there are reports in younger individuals: a 12-year-old reported by Turgut and Kobat [ 8 ] and a 27-year-old reported by Gallo et al [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CM is predominantly observed in the middle age to older Caucasian women [ 4 ]. However, there are reports in younger individuals: a 12-year-old reported by Turgut and Kobat [ 8 ] and a 27-year-old reported by Gallo et al [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports in younger individuals: a 12-year-old reported by Turgut and Kobat [ 8 ] and a 27-year-old reported by Gallo et al [ 2 ]. It can either be asymptomatic or can cause metamorphopsia due to foveal involvement [ 2 , 4 ], often unilateral or rarely bilateral [ 2 ]. Our report demonstrates highly branching CM on ICGA, which was not previously described in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otero-Marquez et al 7 reported a possible association of CM with myopia. They reviewed the fundus images of 13 cases of CM and identified features of high myopia, including fundus tessellation and peripapillary atrophy in 11 of these patients.…”
Section: Article In Pressmentioning
confidence: 99%